Modified ligation of intersphincteric fistula tract versus fistulectomy with primary sphincteroplasty in complex anorectal fistulas - García-Félix, Itzel G.; Vega-Chavarría, Eduardo I. (International Surgery Journal, 2025)
Background: Anorectal fistulas are a common condition with an incidence of 8.6%. The goal of treatment is to control sepsis, preserve continence, and prevent recurrence. The treatment is surgical and there are various surgical techniques. Methods: A retrospective cohort study was conducted. Patients with complex anorectal fistulas were grouped based in surgical procedure, modified ligation of intersphincteric fistula tract (LIFT) (group A) versus fistulectomy with primary sphincteroplasty (group B) at a tertiary care center from 2021 to 2024. Statistical analysis was described with percentages and measures of central tendency, and comparisons between groups were performed with chi-square test, using perfect statistical professional presented (PSPP) 25. Results: Of the 70 patients studied, 30 underwent group A and 40 in group B. The mean age was 45 years, higher incidence in men (71.40%), with risk factors of diabetes (30%), smoking and a history of anorectal surgery (8.60%). Group A had a lower success rate and higher recurrence (76.66% versus 80%, and 20% versus 15%), however, group A had shorter hospital stays (1.6 days versus 2 days, p<0.000), a higher percentage of asymptomatic patients postoperatively (20% versus 15%, p<0.000), shorter healing times (60.33 days versus 65.05 days), and greater fecal continence (93.30% versus 87.5%, p<0.000). Conclusions: Fistulectomy with primary sphincteroplasty is a good surgical option. However, the modified LIFT procedure showed similar success and recurrence rates, with shorter hospital stays, better pain management, shorter healing times, and greater fecal continence, improves patients' quality of life.